Gut Microbiome Homeostasis and the CD4 T- Follicular Helper Cell IgA Axis in Human Immunodeficiency Virus Infection - Onabajo, Olusegun O.; Mattapallil, Joseph J. (Frontiers in Immunology, 2021)
Human Immunodeficiency Virus (HIV) and Simian Immunodeficiency Virus (SIV) are associated with severe perturbations in the gut mucosal environment characterized by massive viral replication and depletion of CD4 T cells leading to dysbiosis, breakdown of the epithelial barrier, microbial translocation, immune activation and disease progression. Multiple mechanisms play a role in maintaining homeostasis in the gut mucosa and protecting the integrity of the epithelial barrier. Among these are the secretory IgA (sIgA) that are produced in vast quantities throughout the mucosa daily and play a pivotal role in preventing commensal microbes from breaching the epithelial barrier. These microbe specific, high affinity IgA are produced by IgA+ plasma cells that are present within the Peyer’s Patches, mesenteric lymph nodes and the isolated lymphoid follicles that are prevalent in the lamina propria of the gastrointestinal tract (GIT). Differentiation, maturation and class switching to IgA producing plasma cells requires help from T follicular helper (Tfh) cells that are present within these lymphoid tissues. HIV replication and CD4 T cell depletion is accompanied by severe dysregulation of Tfh cell responses that compromises the generation of mucosal IgA that in turn compromises epithelial barrier integrity leading to commensal bacteria readily breaching the epithelial barrier and causing mucosal pathology. Here we review the effect of HIV infection on Tfh cells and mucosal IgA responses in the GIT and the consequences these have for gut dysbiosis and mucosal immunopathogenesis.